IMPROVING HISTORY LEARNING OUTCOMES THROUGH "TALKING STICK" MODEL LEARNING IN CLASS XI STUDENTS OF SMA NEGERI 3 MEDAN - Benzisno Josua Simanjorang; Abd Haris Nasution; Masniar Sihotang (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
This research aims to improve the history learning outcomes of class XI students at SMA Negeri 3 Medan through the application of the "Talking Stick" learning model. The research method used is classroom action research (PTK) with two cycles, each consisting of planning, implementation, observation and reflection stages. The research subjects were 35 class XI IPS students. Data was collected through learning results tests, observations and interviews. The research results show that the application of the "Talking Stick" model significantly improves students' history learning outcomes. In the first cycle, the average student score increased from 68.5 to 75.2, and in the second cycle, it increased again to 82.4. Apart from increasing grades, there is also an increase in student activity and participation in the learning process. Students become more active in discussions and dare to express their opinions. The "Talking Stick" model has proven effective in increasing students' understanding and engagement in history subjects. Based on these findings, it is recommended that history teachers at SMA Negeri 3 Medan and other schools consider using the "Talking Stick" learning model as an alternative learning strategy to improve student learning outcomes. In addition, further research is recommended to examine the application of this model to different subjects and educational levels